Prosopographical Method and Data of Central, Administrative, and Judicial Officers of the GDL in the Lithuanian Metric, 1528–1564 - Vaitkus, Tomas (Lietuvos istorijos studijos, 2022)
In the digital age, databases are becoming a much more valuable recource for historians. From the abstract perspective, as an archive of the Grand Duchy of Lithuania, the Lithuanian Metrica has signs indicating that it is a massive database. Appropriate methods are needed to command such a large amount of information. A prosopography questionnaire lets us pick up data points from the Lithuanian Metrica, which is very useful for researching groups of persons from the governing body of the Grand Duchy of Lithuania. For example, with the help of a prosopographical questionnaire, we can extract specific data – personal, biographical, political career, social, economical – regarding officers who served under the Grand Duchy of Lithuania in the sixteenth century. LM’s judicial documents, privileges, and testaments are a great source of data for onomastics and reconstructions of marital statuses and social networks. Testaments also accurately indicate dates of death as well as the economical capital of the deceased. Military lists also give us a massive amount of information regarding the economical and political influence of a person. Unfortunately, the amount of type of sources are inconsistent, and a lot of persons from the researched group have “blind spots” on their prosopographical questionnaires. This reason can be partially resolved, as different types of sources in the LM can provide similar data, and thus make the prosopographical method a very useful tool for working with the LM.
Keywords: prosopography; Lithuanian Metric; digital database; questionnaire